Inflation Persistence and Volatility Dynamics in Pakistan: Empirical Evidence and Policy Insights - Bushra Pervaiz; Muhammad Qasim Manzoor; Muhammad Faisal Majeed (Journal for Social Science Archives, 2025)
Inflation and its volatility pose persistent risks for Pakistan’s macroeconomic stability. Using monthly data from February 2021 to June 2024, this study examines the determinants of inflation and models its conditional volatility. The empirical strategy combines unit-root tests, ARCH-family models (GARCH, TGARCH, EGARCH), and Granger causality. In the mean equation, inflation is highly persistent (lagged coefficient ≈ 0.72, p < 0.01). Exchange-rate depreciation raises inflation materially (≈ 0.15–0.18, p < 0.05), while money supply has a modest effect and exports are small or insignificant in most specifications. Volatility estimates confirm clustering and high persistence: in GARCH(1,1), α+β is close to unity (≈ 0.91), indicating long-lasting shocks. TGARCH detects asymmetry, with negative and positive shocks affecting volatility differently. The EGARCH model fits best (AIC ≈ 1.742), capturing asymmetry, highlighting the strong role of the exchange rate, and a weaker effect of exports. Granger tests reveal bidirectional links between inflation and its volatility at longer lags, consistent with a feedback cycle in which high inflation breeds uncertainty and uncertainty raises inflation. Exchange-rate depreciation Granger-causes inflation, while money supply and exports show no short-run causal effects. Overall, inflation in Pakistan is persistent, exchange-rate sensitive, and volatility-driven. The evidence supports policies that stabilize the exchange rate, improve monetary transmission, and strengthen export competitiveness to anchor expectations and reduce price volatility.